ANALISIS LAMA MENCARI KERJA BAGI TENAGA KERJA TERDIDIK DI KABUPATEN PURWOREJO - Kurniawan, Azhar Putera; Handayani, Herniwati Retno (Diponegoro Journal of Economics, 2013)
There are imbalance between the number of labor force with the number of jobs made a fairly high unemployment. One of condition to participate into labor market was education which could increase productivity of work and have a influence on the opportunities to get a job. Moreover, the higher education level of the job seekers are the higher the reservation wage, so that the longer they are looking for a job. Unemployed educated labor only happened during they are looking for a job that known as frictional unemployment.The purpose of this research was to analyze the job seeking period for educated employment in the Purworejo district. The variables in this research studied were education level, age, salary, and employment status. While, the object of the research was educated employment who working in Purworejo as many as 100 people. And the type of data collected were the primary data and secondary data. Moreover, the methods of data analysis used in this research was the analysis of multiple regression double-log.The results of this research shows that of the four independent variables, education level, age, salary, and employment status influences significantly to job seeking periode for the educated labor with the value of the F-test was 33,006. With the value of Adjusted R square was 0,564, it means education level, salary, age and employment status were able to explained job seeking periode variations 56,4 percent and 43.6 job seeking periode can be explained by other variables that were not included in this research analysis model.